Cover Image. (10th August 2021) - Dharmarajan, Guha; Gupta, Pooja; Vishnudas, C. K.; Robin, V. V.
Abstract : The cover image is based on the Letter Anthropogenic disturbance favours generalist over specialist parasites in bird communities: Implications for risk of disease emergence by Guha Dharmarajan et al., https://doi.org/10.1111/ele.13818 . Image Credit: Ian Lockwood.